PRIORITY DIRECTIONS OF DEVELOPMENT OF MODERN EDUCATION SYSTEM (Eureka Journal of Education & Learning Technologies, 2026)
This article analyzes the development directions of the modern education system, its role in the development of society, and mechanisms for improving the quality of education. The study considers the issues of modernization of the education system, introduction of innovative pedagogical approaches, and integration of digital technologies into the educational process. It also substantiates the strategic importance of the education system in improving the efficiency of educational management and developing human capital. The results of the study serve to develop scientific and practical recommendations aimed at improving the educational process.
Keywords: Education system, innovative education, pedagogical technologies, digital education, quality of education, modernization, human capital, educational management.